2017
DOI: 10.1149/2.0071713jes
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of NiMoS4for High-Performance Hybrid Supercapacitors

Abstract: Transition metal sulfides have been suggested as promising materials for efficient energy storage with superior electrochemical performances. Compound NiMoS4-A was synthesized by a facile chemical co-precipitation process, followed by calcining at 450 o C in Ar. The asprepared NiMoS4-A electrode exhibits a high specific capacity of 313 C g -1 at 1 A g -1 and good rate capability (83% retention at 10 A g -1 ). Electrochemical impedance spectroscopy (EIS) results indicate that the good performances could be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…As shown in Figure D, the diffusion‐controlled Faradic contribution can occupy 85% of total charge at a low scan rate of 1 mV/s, which then decreases with increasing scan rate, reaching 56% at a high‐scan rate of 20 mV/s. The Faradaic redox process dominates at lower scan rates while the capacitive effect at higher scan rates, which is similar with the previous report …”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…As shown in Figure D, the diffusion‐controlled Faradic contribution can occupy 85% of total charge at a low scan rate of 1 mV/s, which then decreases with increasing scan rate, reaching 56% at a high‐scan rate of 20 mV/s. The Faradaic redox process dominates at lower scan rates while the capacitive effect at higher scan rates, which is similar with the previous report …”
Section: Resultsmentioning
confidence: 59%
“…The electrochemical behaviors of the assembled hybrid devices were recorded in a two‐electrode architecture. The specific capacity ( C M or C′ M , mAh/g), energy ( E , Wh/kg), and power ( P , W/kg) were determined in the light of Equations C=i×t3.6×m italicCs=i×tv×m CM=i×t3.6×M CM=i×normaldV3.6×M×S×V E=CM×V20.25em P=3600×Et where i (A) and Δ t (s) refer to the discharge current and time; Δ v (V) and m (g) are the potential range and quality of the active materials in a single electrode; Δ V (V), S (V/s), and M (g) correspond to the potential range, scan rate, and total quality of the active materials for the device, respectively.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…when these is lack of renewable supply) [16]. Among these value-added products, carbon monoxide (CO) [17,18], hydrocarbons (CH4 or C2H4) [19,20], alcohols (CH3OH or C2H6O) [21,22] or formic acid (HCOOH) [23,24] can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…). [68][69][70][71][72][73][74] It is worth mentioning that conducting polymers, as an important class of Faradaic materials, can exhibit both pseudocapacitive and battery-type charge storage. A recent in situ atomic force microscopy study revealed the hybrid battery-pseudocapacitive behavior of conducting polymers in ionic liquids, where the conducting polymers demonstrate pseudocapacitive behavior at a high charging condition, and a battery-type behavior at a low charging condition.…”
mentioning
confidence: 99%